Literasi Digital dan Ancaman Cybergrooming: Tingkat Pemahaman Siswa Sekolah Dasar - Alfatih, Ainun Najib; Azis, Innayah; Fachri, Fidia Maulidka Maisha; Wahab, Nurmi Azzahra; Tahir, Dhea Anatasya; Fahri, Muhammad (INSIGHT: Indonesian Journal Social Studies and Humanities, 2025)
Abstract. The advancement of digital technology necessitates the strengthening of digital literacy from an early age, particularly in elementary school, to help students navigate the risks of online interactions such as cyber grooming. This study aims to develop an interactive learning media called Cyber Smart Kids as an educational tool to enhance students’ understanding and awareness of the dangers of cyber grooming. The research employed a Research and Development (R&D) method using the ADDIE model, which includes the stages of needs analysis, media design, product development, implementation, and evaluation. Data were collected through interviews, observations, questionnaires, expert validation, as well as pretests and posttests conducted in five elementary schools in Parepare City. Statistical tests showed that the data were normally distributed and there was a significant difference between pretest and posttest scores (t = -18.686; p < 0.05), with an average increase of 21.02 points. These findings indicate that Cyber Smart Kids is effective in improving students’ understanding of the concept, forms, and prevention of cyber grooming, while also promoting a positive attitude towards safe and responsible internet use. This media product is expected to serve as a reference for innovative learning based on digital literacy and character education, and to support elementary schools in creating a safe digital environment for children. Keywords: cyber grooming, instructional media, education.